Security analysis of measurement-device-independent quantum conference key agreement with weak randomness - Jiang, Xiao-Lei; Wang, Yang; Lu, Yi-Fei; Li, Jia-Ji; Zhang, Hai-Long; Jiang, Mu-Sheng; Zhou, Chun; Bao, Wan-Su (Frontiers in Physics, 2023)
Quantum conference key agreement (QCKA) allows distributing secret conference keys among multiple users over long distances. Measurement-device-independent QCKA (MDI-QCKA) is an effective QCKA scheme, which closes all detection loopholes and can greatly enhance QCKA's security in practical application. However, an eavesdropper (Eve) may compromise the security of practical systems and acquire conference key information by taking advantage of the weak randomness from the imperfect quantum devices. In this paper, we analyze the side effects of weak randomness on MDI-QCKA. Our simulation results show that even a small proportion of weak randomness may lead to a noticeable fluctuation on the conference key rate. For the case with finite-key size, we find that the weak randomness damages the performance of MDI-CKA in different degrees according to the size of total pulses data transmitted. Furthermore, we infer that the QCKA based on single-photon interference technology may perform better in resisting weak randomness vulnerabilities. Our work contributes to the practical security analysis of multiparty quantum communication and takes a further step in the development of quantum networks.